PENGEMBANGAN PELUMAS RAMAH LINGKUNGAN DENGAN ESTER BORAT - Dicky Dermawan; Jono Suhartono (Teknoin, 2016)
This paper reports an attempt to improve the performance of environmentally friendly bio-based lube oil prepared from glycerol and oleic acid. Four variant of boric acid esters, fortified with 2,5dimercapto-1,3,4-thiadiazol, aromatic amine antioxidant, and benzotriazol were used as additives. The oxidation & corrosion test was carried out using the bulk test at 150oC for 24 h. Steel & copper specimens weight losses and kinematic viscosity increase (measured at 40oC and 100oC according to ASTM D-445) were used to measure the effect of formulation to the corrosiveness and oxidation stability of the oil, respectively. Experimental results indicated that nitrogen-containing boric acid esters showed better performance in terms of oxidation stability improvement. Slight increases in corrosiveness were shown for all additive systems. Phenyl-1-naphtylamine showed better performance than diphenylamine antioxidant.